Distributed rate adaptive packet access (DRAPA) for multicell wireless networks. - Yin, H. (IEEE Transactions on wireless communications)
Fueled by the explosive growth of the Internet, applications are demanding higher data rates and better services. Given the scarcity of radio resources, higher network capacities need to be achieved through more efficient use of the available bandwidth. Current cellular networks utilize frequency planning schemes that are optimized for circuit-switched applications, and thus is inherently problematic for future wireless packet networks with bursty, high peak-rate traffics. Random access schemes such as the ALOHA are seen as better solutions for packet networks. However, co-channel interference may significantly reduce the network throughput when the multicell load is heavy. In this paper, we propose a distributed rate adaptive packet access (DRAPA) scheme to combine the advantages of rate adaptation (in circuit-switched networks) and random access (in packet-switched networks). In particular, DRAPA allows terminal stations to transmit packets in random access fashion in the presence of brusty interference from neighboring cells. The packet code rate is adjusted according to interference level so that the retransmisson is controlled at an acceptable level. The DRAPA scheme subsumes two traditional schemes as the extreme cases, and has superior performance over the traditional schemes in terms of throughput and stability.